The effect of parenteral nutritional repletion on muscle water and electrolytes. Implications for body composition. - Starker, P M (1983)
Nutritional depletion and repletion are associated with changes in the size of the extracellular and intracellular fluid compartments. Although the effect of nutrition on whole body composition is well established, the distribution of changes among the various body tissues is not. This study correlates changes in skeletal muscle composition with whole body electrolyte and nitrogen balance in an attempt to establish the contribution made by skeletal muscle to the changes in whole body fluid and electrolyte composition. Total parenteral nutrition was administered to ten patients for 16 to 25 days. Oxygen consumption, CO2 production, and balances of N, Na, and K were measured daily. Muscle biopsies were taken prior to administration of TPN, in the middle, and at the end of the nutritional regimen. Prior to administration of parenteral nutrition, muscle concentrations of water, sodium, and chloride were significantly higher than normal. With institution of the nutritional support regimen, all three concentrations decreased. The calculated loss in muscle water could account, at most, for only one-sixth of the loss in total body water. Muscle Na loss could account for approximately one-half of the whole body change. Potassium concentrations in the depleted patients were not significantly decreased from normal values and showed a negligible increase with TPN. Since the ratio of K to dry fat-free solids in muscle was constant, most of the whole body changes could be accounted for by assuming that nearly all N is deposited in muscle. Nutritional support results in restoration of cell mass with a contraction of the extracellular fluid (ECF) compartment. The changes in the ECF must occur in tissues other than muscle, while the restoration of cell mass occurs primarily in muscle.